The Effect of Service Quality, Price Perception, and Location on Customer Satisfaction at Harris Suites Fx Sudirman Hotel - Chatarina Yunita Tarigan; Misne Azimatul Ikhsania (Institute of Computer Science (IOCS), 2021)
This study analyzes service quality, price perception, and location on customer satisfaction at Hotel Harris Suites fX Sudirman Jakarta. The type of data in this study is primary data or data from respondents containing respondents' opinions of service quality, price perception, and location on customer satisfaction. Data collection can be found questionnaire instrument. The population in this research is customers of Hotel Harris Suites fX Sudirman Jakarta with a sample of 100 respondents by Purposive Sampling. The method of analysis uses descriptive and quantitative methods. The calculated value is more significant than the t table from the research results on partial variables. This study shows and states a positive and considerable influence of service quality, price perception, and location on customer satisfaction. At the same time, the percentage of impact on service quality, price perception, and place on customer satisfaction at Hotel Harris Suites fX Sudirman Jakarta amounted to 78.4%. In contrast, the rest is influenced by others.